Regulasi Konflik Pemilu (Studi Kasus Resolusi Konflik Pilkada 2015 dan Persiapan Pemilu 2019 di Kabupaten Sijunjung) - Sri Anggraini; Afrizal Afrizal; Indradin Indradin (Jurnal Antropologi: Isu-Isu Sosial Budaya, 2019)
In the election, the conflict will always exist. Whether it is a conflict between the election participants, between the participants and the election organizers or among the election organizers itself. The purpose of this research is to analyze the contribution of the Election Conflict Regulation on handling the election conflict in Sijunjung Regency and to analyze the response of the conflicting parties to the usage of the Election Conflict Regulation in Sijunjung District. This research used a qualitative approach with a case study plan. To see this problem, the researcher used Ralf Dahrendorf's Conflict Theory of Regulation which explains that conflict regulation can affect the high and low escalation of conflicts that occurred. The results showed that in the resolution of conflicts that had occurred both in the 2015 Regional Heads Election conflict or the conflict during the preparation of the 2019 General Election, researcher found that the General Election Conflict Regulation played a role / contributed in resolving the conflicts, where the conflicts could be controlled and resolved properly without any increase in violence. This was proven by the conflicting parties that accepted the decision given by the authorities in its settlement plus there were no other conflicting actors involved in the conflict.